Status and prospects for improving yam seed systems using temporary immersion bioreactors - Balogun, M.; Maroya, N.; Asiedu, Robert (Academic Journals, 2014)
Yam production is constrained by scarcity of clean seed, pests, diseases and low soil fertility in the informal seed system, which is still operational, causing up to 90% yield losses. Although meristem culture can be effective for producing healthy seed yam, its use is limited by slow rate of regeneration and propagation in conventional tissue cultures. In most crops tested, temporary immersion bioreactor systems (TIBs) increased propagation rates. To determine the potential of TIBs in improving the yam seed system, 23 databases were consulted and three returned a total of eight publications with only 2 for Dioscorea rotundata-cayenensis. Both plantlets and microtubers can be produced in TIBs, which will facilitate production of quality breeder, foundation and certified seeds and fast-track genetic improvement and the evolution of a formal from informal seed production system. Control of contamination, direct use of field explants, culture of micro-explants like immature embryos and anthers, increasing the size of microtubers produced and standardization for various economically important yam genotypes are knowledge gaps that require immediate research attention. No report has put a cost on yam TIBs, but it will be necessary to use cost-effective TIBs to encourage integration public-private partnerships into emerging formal seed system.